2010
DOI: 10.1080/02680513.2010.511949
|View full text |Cite
|
Sign up to set email alerts
|

Using netbooks to support mobile learners’ investigations across activities and places

Abstract: We explore how small format laptops ('netbooks') have been used within evidence based investigations undertaken by secondary school students, to what extent these are suitable for effectively supporting learners across different locations and contexts, and their implications for open learning. Over the course of seven trials with 300 students and seven teachers we have gathered data on how netbooks have been used in formal and informal learning contexts, bridging school, field locations, and home. The netbooks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A research study with secondary school learners shows that their mobile devices afford them mobility to work on an activity in different settings. Participants adopted a notebook computer for the study and they assisted one another when technical problems arose; this could be regarded as a mobile social support group (Gaved et al 2010 :187).…”
Section: Mobile Devices As a Communication Toolmentioning
confidence: 99%
“…A research study with secondary school learners shows that their mobile devices afford them mobility to work on an activity in different settings. Participants adopted a notebook computer for the study and they assisted one another when technical problems arose; this could be regarded as a mobile social support group (Gaved et al 2010 :187).…”
Section: Mobile Devices As a Communication Toolmentioning
confidence: 99%
“…If it is understood that mobile devices can support academic staff in their research (e.g. Mackerron, 2010) and in the task of inducting students into inquiry approaches to learning (see Gaved et al, 2010), these could be strong reasons for greater personal engagement with what mobile technologies have to offer.…”
Section: Proposal: Faculty As Lifelong Learnersmentioning
confidence: 99%
“…Different mobile devices can support different applications. In investigation [20] carried out in regard to the use of net books as a single device to support a range of learning activities associated with mobile learners it is concluded that a separate optimal device for each activity can ensure the adoption and sustainability of mobile learning.…”
Section: Mobile Learningmentioning
confidence: 98%